CALISTUNG STUDIO TO IMPROVE LITERACY AND NUMERACY OF JUNIOR HIGH SCHOOL STUDENTS - Haroky, Faruq; Lihayati, Rifa; Septania, Nadia Luanda (Kopertis Region IV Jabar and Banten, 2025)
Literacy and numeracy skills are very important basic competencies for Junior High School students. However, the results of a national survey show that many students in Indonesia are still below the expected literacy and numeracy standards. One approach that can be used to overcome this problem is the implementation of a calistung studio, a learning program that focuses on improving reading, writing, and arithmetic skills. This research aims to evaluate the effectiveness of the studio calistung program in improving junior high school students' literacy and numeracy skills. This research uses a quasi-experimental approach with an AKM pre-test and post-test design. A total of 10 eighth grade students at a private junior high school participated in this study. Data were collected through literacy and numeracy tests before and after the implementation of the calistung studio program. The increase in student abilities was measured based on the results of the pre-test and post-test. The results showed an increase in both aspects studied. Students' literacy skills increased from 34% in the pre-test to 42% in the post-test. Meanwhile, numeracy skills increased from 14% in the pre-test to 20% in the AKM post-test. The calistung studio program has contributed positively to improving junior high school students' literacy and numeracy skills, although the increase is still relatively small. Further improvements are needed to extend the duration and provide intensive assistance for students who experience difficulties.